Juridical Analysis Of The Implementation of The BPJS Kesehatan Program in Improving Access to Health Sevices in Indonesia - Meri Ulfa; Marice Simarmata; Irsyam Risdawati (Journal Evidence Of Law, 2026)
Healthcare is a constitutional right guaranteed by the 1945 Constitution of the Republic of Indonesia, yet access disparities remain a serious problem in Indonesia. This study aims to analyze the legal aspects of implementing the BPJS Kesehatan program to improve access to health care and identify existing legal barriers. The research method employs a normative legal approach, using statutory and conceptual frameworks, and analyzes primary,secondary, and tertiary legal materials through a qualitative, descriptive-analytical approach. The results indicate that the BPJS Health program has a strong legal foundation based on the 1945 Constitution of the Republic of Indonesia, Law No. 40 of 2004 on the National Social Security System, Law No. 24 of 2011 on the Social Security Administration Agency, and Law No. 17 of 2023 on Health, with an enrollment coverage of 89% of the population (242 million people).However, implementation faces legal challenges: a gap between regulations and practice, a financial deficit of Rp 13 trillion, delays in claim payments, and weak legal protection for participants. The study recommends regulatory reform, improvements to the financial system,strengthening of legal protection mechanisms, and enhanced coordination among institutions to achieve equitable and sustainable Universal Health Coverage.